2017
DOI: 10.1038/s41598-017-17407-w
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent Regulation of Alternative Cleavage and Polyadenylation During Hippocampal Long-Term Potentiation

Abstract: Long-lasting forms of synaptic plasticity that underlie learning and memory require new transcription and translation for their persistence. The remarkable polarity and compartmentalization of neurons raises questions about the spatial and temporal regulation of gene expression within neurons. Alternative cleavage and polyadenylation (APA) generates mRNA isoforms with different 3′ untranslated regions (3′UTRs) and/or coding sequences. Changes in the 3′UTR composition of mRNAs can alter gene expression by regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 86 publications
(81 reference statements)
6
41
0
Order By: Relevance
“…We found that following an epoch of enhanced neuronal activity, the 3 0 UTR isoforms in both compartments, the somata and the neuropil, were altered, with an overall shortening of 3 0 UTRs observed. A shortening of 3 0 UTRs was recently reported in hippocampal slices following a chemical-LTP protocol (Fontes et al, 2017). Most of the activity-dependent changes in 3 0 UTR isoforms were transcription dependent, consistent with alternative polyadenylation identified as an important mechanism for diversifying 3 0 UTRs in both dendrites (Fontes et al, 2017) and developing axons (Shigeoka et al, 2016;Zhang et al, 2016).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…We found that following an epoch of enhanced neuronal activity, the 3 0 UTR isoforms in both compartments, the somata and the neuropil, were altered, with an overall shortening of 3 0 UTRs observed. A shortening of 3 0 UTRs was recently reported in hippocampal slices following a chemical-LTP protocol (Fontes et al, 2017). Most of the activity-dependent changes in 3 0 UTR isoforms were transcription dependent, consistent with alternative polyadenylation identified as an important mechanism for diversifying 3 0 UTRs in both dendrites (Fontes et al, 2017) and developing axons (Shigeoka et al, 2016;Zhang et al, 2016).…”
Section: Discussionsupporting
confidence: 72%
“…A shortening of 3 0 UTRs was recently reported in hippocampal slices following a chemical-LTP protocol (Fontes et al, 2017). Most of the activity-dependent changes in 3 0 UTR isoforms were transcription dependent, consistent with alternative polyadenylation identified as an important mechanism for diversifying 3 0 UTRs in both dendrites (Fontes et al, 2017) and developing axons (Shigeoka et al, 2016;Zhang et al, 2016). Surprisingly, though, a substantial fraction ($25%) of activity-induced changes in 3 0 UTR isoforms were independent of transcription.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…To quantify APA, DEXseq (https://doi.org/doi:10.18129/B9.bioc.DEXSeq) was employed (following previously published workflows for APA analysis (Rot et al, 2017;Fontes et al, 2017). Genes from the analysis set which had at least two alternative active PAS (7718 genes) were subject to differential PAS usage quantification with DEXSeq.…”
Section: Quantification Of Alternative Polyadenylation (Apa)mentioning
confidence: 99%
“…The bioinformatics pipelines for APA processing described above have been well tested by the scientific community 24 , 32 - 35 . Figure 2 demonstrates the bioinformatics pipelines we have developed to analyze our WTTS-seq datasets 1 , 14 , 36 - 37 .…”
Section: Bioinformatics Pipelines For Apa Characterizationmentioning
confidence: 99%